Cognitive Behavior Therapy (CBT) Pada Pasien Pasca Stroke dengan Depresi Literatur Review - Santi Rinjani; Suryani Suryani; Aat Sriati; Andri Nugraha (STIKes Karsa Husada Garut, 2021)
Stroke is one of the most serious diseases because of the death and mortality rate. The World Health Organization (WHO) revealed that stroke is the second leading cause of death in the world, killing 6.2 million people. Half of all have problems returning to their pre-stroke state in their daily routine. Especially the psychosocial problems of stroke survivors have a negative impact on their quality of life, causing depression. The level of anxiety and depression can be reduced by means of the patient being given therapy, namely Cognitive Behavior Therapy. This literature search aims to analyze the results of research that focuses on the effect of Cognitive Behavioral Therapy on helplessness, depression in stroke patients. Method This study was conducted by reviewing the literature through electronic media on Sience Direct and Google Scholar and using the keywords